IN VITRO ANTIOXIDANT AND ANTICANCER ACTIVITY OF MACRANGA PELTATA LEAF EXTRACTS ON LUNG CANCER CELL LINES - ANIL, LINA; MOHANDAS, S. (International Journal of Current Pharmaceutical Research, 2023)
Objective: To determine the phytochemical constituents, antioxidant and anticancer activities of Macranga peltata leaf extracts on A549 and P 51 human lung cancer cell lines. Methods: Leaf sample was subjected to soxhlet extraction method and phytochemical screening was done using different biochemical tests. The antioxidant activity was tested using 2,2–diphenyl-1-picrylhydrazyl, ferric ion reducing power assay and 2,2–azino bis 3–ethyl benzothiazoline–b–sulfonic acid assay. In vitro anticancer activity on A549 and P 51 human lung cancer cell lines was evaluated by (3-(4,5-dimethyl thiazole-2yl)-2,5–diphenyl tetrazolium bromide) MTT assay. Results: Phytochemical screening confirmed the presence of phytoconstituents like tannins, flavanoids, alkaloids, saponins, glycosides and reducing sugar. The antioxidant assays exhibited significant inhibiting activity. MTT cell proliferation assay of methanolic extract of plant drug produced a cytotoxic effect on lung cancer cell lines A549 and P 51 with an IC50 value of 197.10 µg/ml, while it had no cytotoxic effect on normal cell lines. Conclusion: It has been reported the effect of flavanoid characteristics in reducing the cancer. M. peltata contains a wide variety of secondary metabolites that hold strong antioxidant capacity. Their leaf have found to be potential source of antioxidants and anticancer activity.